2000
DOI: 10.1093/toxsci/55.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cholinergic Neurotoxicity of Oral Chlorpyrifos Exposures in Preweanling and Adult Rats

Abstract: Chlorpyrifos (CPF) is a common organophosphorus (OP) pesticide. Previous studies have demonstrated that neonatal rats are more sensitive than adults to the acute toxicity of high dosages of CPF. The present study examined lethality and age-related differences in neurochemical indicators and functional signs of neurotoxicity following a broad range of acute and repeated oral CPF exposures. There was about a 9-fold difference in sensitivity to the acute-dose lethality of chlorpyrifos among neonatal (7 days-of-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 35 publications
7
59
2
Order By: Relevance
“…In this study, the ratio of brain ChE ED50s for chlorpyrifos was 4.3, similar to the 5-fold difference in maximally tolerated dose (MTD) at PND17 . While others have reported somewhat greater MTDs and LD10s in younger rats (PND7, MTD ratio 6.2-fold, LD10 ratio 9.1-fold; Pope et al 1991;Zheng et al 2000), they found the ratio of brain ED50 values at PND7 to be less (2.2-fold; Pope and Liu 1997) than reported here for older rat pups. In our data, RBC ChE inhibition was not greater in the pups, in contrast to other reports of juvenile sensitivity of around 4-fold (Pope et al 1991;Zheng et al 2000).…”
Section: Organophosphatescontrasting
confidence: 78%
“…In this study, the ratio of brain ChE ED50s for chlorpyrifos was 4.3, similar to the 5-fold difference in maximally tolerated dose (MTD) at PND17 . While others have reported somewhat greater MTDs and LD10s in younger rats (PND7, MTD ratio 6.2-fold, LD10 ratio 9.1-fold; Pope et al 1991;Zheng et al 2000), they found the ratio of brain ED50 values at PND7 to be less (2.2-fold; Pope and Liu 1997) than reported here for older rat pups. In our data, RBC ChE inhibition was not greater in the pups, in contrast to other reports of juvenile sensitivity of around 4-fold (Pope et al 1991;Zheng et al 2000).…”
Section: Organophosphatescontrasting
confidence: 78%
“…Cholinergic Toxicity of Chlorpyrifos Several investigators have shown that young animals are more susceptible than adults to the acute toxicity of chlorpyrifos (Pope et al, 1991b;Whitney et al, 1995;Moser et al, 1996;Zheng et al, 2000). For example, the LD 50 of chlorpyrifos in neonatal [postnatal day (PND) 7] rats was reported to be 10-fold lower than in adult animals (Zheng et al, 2000).…”
Section: Ivc Age-dependent Sensitivity To the Acutementioning
confidence: 99%
“…The dosages selected were based on the LD 10 (i.e., either vehicle, 0.5 × LD 10 or 1 × LD 10 : neonates = 0, 7.5 or 15 mg/kg; adults = 0, 68 or 136 mg/kg [Zheng et al, 2000]). Functional signs of toxicity were evaluated and rats were euthanized at 4, 24 and 96 hours after treatment.…”
Section: Animal Treatmentsmentioning
confidence: 99%